Loss of trifluralin metabolic resistance in Lolium rigidum plants exposed to prosulfocarb recurrent selection. Issue 12 (7th August 2020) - Busi, Roberto; Goggin, Danica E; Onofri, Andrea; Boutsalis, Peter; Preston, Christopher; Powles, Stephen B; Beckie, Hugh J
Abstract: BACKGROUND: Resistance to the dinitroaniline herbicide trifluralin in Lolium rigidum (annual ryegrass) often is mediated by the enhanced capacity to metabolize the herbicide to less toxic polar conjugates and/or by functionally recessive target‐site mutations in α‐tubulin. RESULTS: In two L. rigidum populations possessing enhanced trifluralin metabolism, resistance was largely reversed by recurrent selection with the thiocarbamate herbicide prosulfocarb (i.e. plant survival was two‐ to >20‐fold lower). Their ability to metabolize trifluralin was significantly decreased (by ≈2.3‐fold) following recurrent prosulfocarb selection, to levels comparable to those observed in susceptible plants or when trifluralin metabolism was inhibited by treatment with the insecticide phorate. CONCLUSIONS: This study provides evidence that trait(s) enabling efficient trifluralin metabolism in L. rigidum are purged from the population under prosulfocarb recurrent selection. The level of trifluralin metabolism in vitro and its inhibition caused by phorate action on trifluralin‐metabolizing enzyme(s) is equivalent to the effect produced by prosulfocarb selection. The hypothetical link between the two phenomena is that the putative monooxygenase(s) conferring trifluralin metabolic resistance also mediate the activation of prosulfocarb to its toxic sulfoxide. Thus, we speculate that survival to prosulfocarb via a lack of metabolic herbicide activation, and survival to trifluralin conferred by enhanced herbicide metabolism, are mutually exclusive. These findings not only open up a new research direction in terms of the interaction between different herbicide resistance mechanisms in L. rigidum, but also offer strategies for immediate management of the population dynamics of metabolism‐based resistance in the field. © 2020 Society of Chemical Industry Abstract : Trifluralin metabolic resistance can be inhibited by treatment with the insecticide phorate (yellow arrow) or purged under recurrent selection with the herbicide prosulfocarb (green arrow).